Ice drift - Taylor, Theodore, 1921-2006. (Orlando, Fla. : Harcourt, 2006)
In 1863, two young Inuits, fourteen-year-old Alika and his younger brother Sulu, must fend for themselves during the six months they are stranded on an ice floe drifting south from Ellesmere Island towards the Greenland Strait.
5.0
3-6
3-6
School Library Journal
Book Links (A.L.A.)
Booklist
Keywords: Inuit -- Fiction; Brothers -- Fiction; Survival -- Fiction; Icebergs -- Fiction; Eskimos -- Fiction; Baffin Bay (North Atlantic Ocean) -- History -- 19th century -- Fiction; Historical fiction; Inuit -- Fiction; Brothers -- Fiction; Survival skills -- Fiction; Icebergs -- Fiction; Baffin Bay (North Atlantic Ocean) -- History -- Fiction; Historical fiction